Dominance and Epistasis Interactions Revealed as Important Variants for Leaf Traits of Maize NAM Population - Monir, Md. M.; Zhu, Jun (Frontiers in Plant Science, 2018)
Leaf orientation traits of maize (Zea mays) are complex traits controlling by multiple loci with additive, dominance, epistasis, and environmental interaction effects. In this study, an attempt was made for identifying the causal loci, and estimating the additive, non-additive, environmental specific genetic effects underpinning leaf traits (leaf length, leaf width, and upper leaf angle) of maize NAM population. Leaf traits were analyzed by using full genetic model and additive model of multiple loci. Analysis with full genetic model identified 38 ~ 47 highly significant loci (−log10PEW > 5), while estimated total heritability were 64.32 ~ 79.06% with large contributions due to dominance and dominance related epistasis effects (16.00 ~ 56.91%). Analysis with additive model obtained smaller total heritability (18.68 ~ 29.56%) and detected fewer loci (30 ~ 36) as compared to the full genetic model. There were 12 pleiotropic loci identified for the 3 leaf traits: 8 loci for leaf length and leaf width, and 4 loci for leaf length and leaf angle. Optimal genotype combinations of superior line (SL) and superior hybrid (SH) were predicted for each of the traits under 4 different environments based on estimated genotypic effects to facilitate maker-assisted selection for the leaf traits. Keywords: GWAS, maize leaf traits, dominance, epistasis, genomic prediction.